Intersections between Feminist and Queer Theory
XVIII, 192 p.
Keywords: Queer ideas have unsettled other forms of exploring gender and sexuality in particular feminism and feminists have been significant critics. This book explores the debates between feminist and queer theorizing to seek out interconnections and identify new directions in thinking about sexuality and gender that may emerge out of and at the interface.